Effect of Annealing Temperature on Structural, Morphological and Optical Properties of Nanocrystalline TiO2 Thin Films Synthesized by Sol-Gel Dip Coating Method - Manickam, K.; Muthusamy, V.; Manickam, S.; Periyasamy, G.; Senthil, T. S.; Shanmugam, S. (University of Jaffna, 2019)
TiO2 is one of the common materials used for solar cells, diodes, different types of gas sensors, optoelectronic devices, etc. TiO2 is widely used in photovoltaic devices due to interesting optical and electrical properties. In this work, nanocrystalline TiO2 thin films have been prepared by sol-gel dip coating method. X-ray diffraction results showed the formation of anatase phase of TiO2. The SEM is used for analysis of morphology. The EDX analysis confirmed that Ti and O elements are present in the sample. PL and UV-Vis spectroscopy was used for investigation of TiO2 optical properties.
Keywords: Nanocrystalline TiO2; X-Ray Diffraction; Scanning Electron Microscopy; EDAX; UV-Vis; spectroscopy; Photoluminance